Diseminasi Teknologi Mesin Genset Tenaga Surya Bagi Masyarakat Terdampak Bencana Gunung Merapi Desa Wukirsari Kecamatan Cangkringan Kabupaten Sleman - Achmad Buchori; Suwarno Widodo; Sigit Ristanto; Listya Endang Artiani (Universitas Islam Nahdlatul Ulama Jepara, 2019)
The problem experienced by Wukirsari Village as one of the areas affected by the Mount Merapi disaster is the frequent occurrence of PLN power outages. To overcome this problem, the dissemination of technology products to the community aims to improve the ability of Wukirsari villagers to make natural electricity based on solar power and use solar power generator technology and be able to increase the value of sales and marketing. Outputs generated from this activity include the development of a number of group members, training in the use and maintenance of solar generator sets, training in the manufacture of solar engine generator sets, good financial management training and product sales and marketing training. This activity has resulted in: (1) solar generator products that have been carefully prepared with good results by the UPGRIS team, (2) villagers of Wukirsari are able to treat and use properly and correctly, (3) symbolic delivery to 3 residents solar power generator with capacity, 900 Watt, 1200 Watt and 1500 Watt